Perubahan Kultural Masyarakat (Studi Kasus Desa Wisata Pulesari, Dusun Pulesari, Desa Wonokerto, Kecamatan Turi, Kabupaten Sleman, Daerah Istimewa Yogyakarta) - Bella Togiana Limbong; Budi Widayanto; Eko Murdiyanto (Agrisociabus, 2022)
This study aims to (1) Examine the culture of the community before the existence of Pulesari Tourism Village (2) Examine the process of cultural change of the community and community culture after the existence of Pulesari Tourism Village (3) Examine the factors that influence the process of change in Pulesari Tourism Village. This research uses a qualitative approach with a type of case study research. The results of this study show that (1) The culture of the community before the existence of a tourist village was still very traditional and the mindset of the community was not wide so that it was slow to meet the needs of their lives.  (2) The process of cultural change of the people of Pulesari Tourism Village occurs through the process of acculturation and adaptation of cultural ecology, the community has an open mindset and a consumptive lifestyle. However, the elements of art and religious system have not changed (3) Factors that influence the process of change are factors that encourage the process of change that occurs, namely contact with other cultures; advanced formal education system; an attitude of appreciating the results of one's work and the desire to move forward; open system of society; orientation to the future occurs in society; and the value that man must always endeavor. Factors that hinder the course of the process of change that occurs are very traditional societal attitudes and prejudices towards new or foreign things or closed attitudes.Keywords: Community Culture, Cultural Change, Tourism Villages